2011
DOI: 10.1111/j.1365-2265.2011.03984.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of hypothyroidism in TSH deficiency compared to primary thyroid disease: pituitary patients are at risk of under-replacement with levothyroxine

Abstract: Levothyroxine doses were generally under-replaced in pituitary patients compared to primary thyroid disease and the data imply that some untreated patients were actually TSH deficient. The distribution of fT4 in patients with primary thyroid disease on levothyroxine may guide optimum replacement levels in pituitary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 6 publications
1
40
0
4
Order By: Relevance
“…The determination of circulating free thyroid hormone levels is of major significance in monitoring L-T4 treatment in CeH patients (Ferretti et al, 1999;Alexopoulou et al, 2004;Slawik et al, 2007;Iverson and Mariash, 2008;Koulouri et al, 2011;Beck-Peccoz, 2011;Persani, 2012). If blood is withdrawn before the morning administration of L-T4, low free T 4 values may suggest undertreatment and high free T 3 values are more sensitive for disclosing overtreatment.…”
Section: Facts and Uncertainties In Central Hypothyroidism Replacemenmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of circulating free thyroid hormone levels is of major significance in monitoring L-T4 treatment in CeH patients (Ferretti et al, 1999;Alexopoulou et al, 2004;Slawik et al, 2007;Iverson and Mariash, 2008;Koulouri et al, 2011;Beck-Peccoz, 2011;Persani, 2012). If blood is withdrawn before the morning administration of L-T4, low free T 4 values may suggest undertreatment and high free T 3 values are more sensitive for disclosing overtreatment.…”
Section: Facts and Uncertainties In Central Hypothyroidism Replacemenmentioning
confidence: 99%
“…Very recently, Koulouri et al (2011) compared free T 4 values in a large series of patients with hypothalamicpituitary lesions with those of patients with primary thyroid disease adequately treated with L-T4, i.e., those with normal levels of circulating TSH during replacement therapy. The conclusions were that CeH patients The diamonds indicate mean (AEstandard deviation).…”
Section: Facts and Uncertainties In Central Hypothyroidism Replacemenmentioning
confidence: 99%
“…The determination of FT4 acquires a more relevant role in the evaluation of replacement therapy than in primary hypothyroidism. Several groups [49,56,58,60] reported that concentrations of FT4 in the upper part of normal range might represent an appropriate target in most treated CeH patients (Recommendation 26).…”
Section: How Should Ceh Patients Be Managed and Treated?mentioning
confidence: 99%
“…The determination of circulating free thyroid hormone concentrations is of major significance in monitoring L-T4 treatment in CeH patients [1,24,25,49,[56][57][58]. Blood should be withdrawn before or at least 4 h after the L-T4 administration [59].…”
Section: How Should Ceh Patients Be Managed and Treated?mentioning
confidence: 99%
“…In recent years, several papers dealing with substitutive LT4 therapy in patients with CH have been published and all have underlined the pitfalls in achieving optimal replacement because the inability to be guided by serum TSH levels. [8][9][10] The article of Koulouri et al 11 in this issue of Clinical Endocrinology approaches the topic in a new and interesting way. They used their Depatment's clinical information system to identify all patients with hypothalamo-pituitary lesions and divided them into high risk and low risk of CH.…”
mentioning
confidence: 99%